Onkologische Versorgung - was macht die Qualität aus und wie können wir diese erfassen? = Oncological treatment - what constitutes quality and how can this be collated? - Kowalski, Christoph; Post, Stefan (Der Onkologe, 2017)
The study of Kampfenkel et al. investigated whether differences in overall survival could be found in patients with intestinal cancer who were treated in certified centers compared to those treated in non-certified hospitals. We consider some of the limitations of the study, which we believe must be taken into account when interpreting the results of these and similar future studies. Although secondary data evaluations with matched claims and register data can be fundamentally valuable for the description of the health care reality, standards are urgently needed to facilitate the classification of the results and to avoid misleading interpretations.